THE PROBLEM OF CREATING A SYSTEM OF ADVANCED TRAININGOF THE TEACHING STAFF OF TECHNICAL UNIVERSITIES: THE BASIC IDEAS OF THE CONCEPT OF ITS SOLUTION - Vyacheslav M. Prikhod’Ko; Zoya S. Sazonova (Высшее образование в России, 2016)
E analyze the peculiarities of professional pedagogic preparation of scientific% pedagogical staff in technical institutes and universities, characteristic for the Soviet and contemporary Russia. We focus on the solution of the urgent problem of the formation in Russia of an innovational “outpacing” system of engineering%pedagogical preparation of scientific%pedagogical staff members. We analyze the prospects of using the project%targeted approach for its solution. We discuss the main ideas underlying the concept of a network system for the outpacing preparation of modern technical university teachers.